Respuesta :
For this case we have the following system of equations:
[tex]4x-12y = 0\\x + 3y = 7[/tex]
To solve, we follow the steps below:
We multiply the second equation by -4:
[tex]-4x-12y = -28[/tex]
We add the equations:
[tex]4x-4x-12y-12y = 0-28[/tex]
Equal signs are added and the same sign is placed.
[tex]-24y = -28\\y = \frac {-28} {- 24}\\y = \frac {14} {12} = \frac {7} {6}[/tex]
We look for the value of the variable "x":
[tex]x = 7-3y\\x = 7-3 \frac {7} {6}\\x = 7- \frac {21} {6}\\x = \frac {42-21} {6}\\x = \frac {21} {6}\\x = \frac {7} {2}[/tex]
Thus, the solution of the system is:
[tex](x, y): (\frac {7} {2}; \frac {7} {6})[/tex]
Answer:
[tex](x, y): (\frac {7} {2}; \frac {7} {6})[/tex]
Answer:
x= 7/2 y = 7/6
Step-by-step explanation:
4x - 12y = 0
x + 3y = 7
Multiply the second by( -4) to eliminate the X variable
4x - 12y = 0
-4x -12y= -28
ADD BOTH
-24y=-28
Divide both by -24
y= 28/24
y=7/6
Plug y into second equation
x + 3y = 7
x+ 3(7/6) = 7
x+21/6=7
x+7/2=7
x=7-(7/2)
x=( 14/2) - (7/2)
x= 7/2